KETENTUAN YANG MENGATUR TENTANG TINDAK PIDANA PELANGGARAN PENYIMPANGAN SEKSUAL YANG DILAKUKAN OLEH OKNUM MILITER - Azis, Nur Azmi; Simangunsong , Frans (Yustitia, 2024)
In this research, the author's aim is to provide a comprehensive understanding regarding the legal handling of cases of sexual deviation involving military personnel. The author in this research uses normative research methods, with a focus on presenting legal principles, legal rules and legal doctrine that are relevant to answering the legal issues faced. The author in this study will discuss sexual deviation in the context of the military environment. The problem that is the focus of this research is "What are the provisions governing criminal acts of sexual offenses committed by military personnel?" The results that the author hopes in this research will be able to contribute to the refinement of military legalpolicies and the effectiveness of law enforcement in order to prevent and handle sexual violations in the military environment.